Greenbug, Schizaphis graminum (Rondani) (Insecta: Heteroptera: Aphididae) - Gregg S. Nuessly; Russell T. Nagata (EDIS, 2005)
The greenbug, Schizaphis graminum (Rondani), has been recognized as a major pest of small grains for over 150 years. Described by Rondani, it was first placed in the genus Aphis (Rondani 1852) and later moved to the genus Toxoptera. There are about 40 recognized Schizaphis species worldwide with seven known from North America (Blackman and Eastop 2000). This document is EENY-353, one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Published: July 2005.